Prevalence of Depressive Symptoms and Associated Factors in Elderly Primary Care Patients: A Descriptive Study - Magnil, Maria (Physicians Postgraduate Press, Inc., 2008)
BACKGROUND: Depressive symptoms are common in older adults. A majority will be seen in primary care. The aim was to study the prevalence of and to explore factors associated with depressive symptoms in elderly primary care patients. METHOD: In consecutive patients aged 60 years and older attending a Swedish primary care center between February and December of 2003, depressive symptoms were identified as ≥ 13 points on the Montgomery-Asberg Depression Rating Scale–Self-Rated version (MADRS-S). Somatic symptoms measured according to PRIME-MD, age, socioeconomic status, gender, somatic diagnoses, and medication were analyzed in relation to presence of depressive symptoms. RESULTS: Forty-six of 302 patients (15%) rated themselves in the depressed range. There were no differences between depressed and nondepressed patients concerning socioeconomic status, other illnesses, or medication except for use of sedatives/hypnotics being more common (OR = 2.7, 95% CI = 1.3 to 5.6) in depressed patients. Patients in the group scoring ≥ 13 on the MADRS-S were more likely to have become widowed during the last year (OR = 6.0, 95% CI = 1.7 to 20.8) or to have indicated significant life events (OR = 4.3, 95% CI = 2.0 to 9.0), but were less likely to report having leisure time activities (OR = 0.2, 95% CI = 0.08 to 0.41) or perception of good health (OR = 0.1, 95% CI = 0.05 to 0.3). Patients being treated for depression did not have increased depression scores (OR = 1.4, 95% CI = 0.66 to 3.1). CONCLUSION: In a group of unselected primary care elderly patients, the prevalence of depressive symptoms was high. Use of sedatives/hypnotics was remarkably common in patients with depressive symptoms. Patients with ongoing treatment of depression did not have increased depression scores, indicating the good prognosis for treated depression in the elderly.